THE ECONOMIC IMPACT ANALYSIS OF THE INVESTMENT ACTIVITIES DEVELOPMENT ON TRAFFIC SAFETY - Pshinko, O. M. (Science and Transport Progress, 2009)
The indices of train traffic safety on the railways ofUkraineare analyzed. The dynamics of investments to the traffic safety measures on railway facilities is considered.